THE STATUS OF TREATMENT MANAGEMENT AMONG PATIENTS WITH SCHIZOPHRENIA IN PRIMARY HEALTHCARE SETTINGS IN WESTERN HAI PHONG, VIETNAM, 2026 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of treatment management and some factors associated with relapse among patients with schizophrenia in primary healthcare settings in Western Hai Phong, Vietnam, 2026.Methods: A cross-sectional study was conducted on 433 patients. Data were collected through structured interviews and medical record review. Descriptive statistics, Chi-square tests, and univariate odds ratios (OR) with 95% confidence intervals (CI) were applied.Results: The proportion of patients under regular management was 86.9%, while 87.8% received home-based follow-up care and 48.0% were supervised for medication intake. The relapse rate within the past 12 months was 9.9%. No significant association was found between relapse and gender or age (p>0.05). Patients with a treatment duration of ≥40 years had a higher relapse rate compared to those treated for
Keywords: schizophrenia, treatment management, relapse, primary healthcare